A bright shining lie John Paul Vann and America in Vietnam - Sheehan, Neil (Vintage Books, 1989)
250Sheehan's tragic biography of John Paul Vann is also a sweeping history of America's seduction, entrapment and disillusionment in Vietnam. Annotation. Sheehan's tragic biography of John Paul Vann is also a sweeping history of America's seduction, entrapment and disillusionment in Vietnam.